Bioaugmentation-assisted phytoremediation of As, Cd, and Pb using Sorghum bicolor in a contaminated soil of an abandoned gold ore processing plant - Boechat,Cácio Luiz (2020)
ABSTRACT The two main bottlenecks for a successful phytoremediation program are the metal availability in soil and the metal uptake and transfer to shoots of high biomass plants. Several agronomical practices have been tested to boost the bioavailability of metals in soils and accumulation in plants. Here we assessed the feasibility of plant-growth-promoting bacteria (PGPB) isolated from a site contaminated by gold ore processing activities to assist the phytoremediation of As, Cd, and Pb by Sorghum bicolor and mitigate the metal toxicity in plants. The bacteria Kluyvera intermedia, Klebsiella oxytoca, and Citrobacter murliniae were evaluated in single, double, and triple inoculations. They are regarded as metal resistant and were isolated from the rhizosphere of species naturally growing on the metal contaminated site. The treatments comprised two soils (contaminated and non-contaminated) and single (K. intermedia, K. oxytoca, or C. murliniae) or multiple inoculations (K. intermedia + K. oxytoca; K. intermedia + C. murliniae; K. oxytoca + C. murliniae; K. intermedia + K. oxytoca + C. murliniae). Plants were grown for 42 days after inoculation. The results showed that the PGPB K. oxytoca and the combination of K. intermedia + K. oxytoca and K. intermedia + C. murliniae were able to mitigate the metal toxicity in the contaminated soil and hence increase the shoot biomass, with implications to the effectiveness of phytoextraction. The sorghum ability to translocate Cd to shoots in the contaminated soil was enhanced through the single inoculation with K. oxytoca, C. murliniae, and K. oxytoca, as well as by the joint-inoculation with K. oxytoca + C. murliniae, and K. intermedia + K. oxytoca + C. murliniae. Higher accumulation of metals in shoots is a crucial factor in successful phytoextraction. Arsenic and Pb, on the other hand, had their uptake and concentration in roots stimulated by the inoculation. Therefore, regarding these two metals, phytostabilization programs could benefit from the use of the bacteria studied here.